Teius oculatus: Courtship; Mating - Halloy, Monique (2007)
Teius oculatus is a diurnal, oviparous, insectivorous species with a broad distribution in eastern and central Argentina, Uruguay and southeastern Brazil. Save a brief account by Gudynas et al. (1981) courtship and mating are undescribed. Here, we relate behaviors during courtship and mating in both free-ranging and captive T. oculatus (Sauria: Teiidae).